Apicetomy or dental implant: Report of a clinical case. - Enrique Fernández-Bodereau; Patricia Tortolini (Universidad de Concepción., 2012)
We report a clinical case of a patient who underwent apicectomy on an upper premolar, presumably by endodontic done improperly, and have cast a bolt where the extraction run the risk of tooth fracture. Failed such treatment, an implant is performed, placed immediately after extraction, in which bone filling with xenograft and guided bone regeneration with resorbable collagen membrane was done. From this we deduce that the phase diagnosed is of paramount importance. Two months after functional load of the implant is made with a cemented ceramic crown. One of the factors that influenced the positive outcome of this case, where immediately implants are placed to the tooth extraction is ultra microtextured surface of the used implant, besides being the bone table of these dental elements of thicker vestibular.